KAJIAN DESAIN DINING SET MID CENTURY DENGAN SISTEM KNOCK-DOWN STUDI KASUS NEW ELEGANT, LTD. - Susi Hartanto; Aditya Cipta Sugandha (Ide dan Dialog Desain Indonesia (Idealog), 2018)
Mid century is one of furniture style which is quite difficult to be made knock-down for its slim structure. With market high demand of this particular style, furniture company needs to always release new designs with added value. One of added values is knock-down system. Knock-down is generally applied in furniture for space saving. A Case study is taken at New Elegant, Ltd., Vietnam, a furniture company focuses more on dining sets. Mid century dining chair design which can be produced at this company should have 3 basic constructions similar to factory standards (seat frame, front legs, chair back). While dining table design should have table top and table legs assembled with hardware (with or without apron). Forms of design is relative, adjusting to mid century design characteristics, rounded and slim. Quotation price should be in retail price rangeof USD90-99 per piece, and according to cost estimation, designs proposed are within this range.In terms of loadibility, knock-down designs in this research are 48% more efficient in space compared to those with non knock-down structure.Thus, this design model could be a reference on how to modify knock-down mid century designs